Socioeconomic disparities in mortality from indoor air pollution: A multi-country study. - Muayad Albadrani (PLoS ONE)
Background Indoor air pollution is a major public health concern, contributing to approximately 2.9 million deaths and 81.1 million disability-adjusted life years lost annually. This issue disproportionately affects underprivileged communities that depend on solid fuels for cooking. As a result, these communities suffer from heightened exposure to indoor air pollutants, which increases the risk of morbidity, mortality, and worsening health disparities. Objective This study investigates the association between socioeconomic status and mortality related to indoor air pollution across multiple countries. Methods Data from the 2019 Demographic and Health Survey, WHO, and World Bank were utilized to examine the impact of socioeconomic status on indoor air pollution-related mortality. The primary outcome was mortality associated with solid fuel use, with income quintiles as the independent variable. Linear and logistic regression analyses were applied to assess these relationships. Results Logistic regression analysis revealed a strong negative association where household income increases and indoor air pollution-related mortality significantly decreases. Specifically, Households in the highest income quartile showed a 22% reduction progressively in the odds of mortality risk compared to the lowest income quintile. Additionally, access to clean fuel correlated with a 0.59 times lower odds of mortality, highlighting the clean energy sources' protecting effect. Conclusion The findings highlight the critical need to prioritize clean fuel access, particularly in low-income communities, to reduce indoor air pollution mortality. Policies should focus on increasing clean energy accessibility and supporting vulnerable populations through targeted subsidies and poverty alleviation programs to reduce indoor air pollution exposure disparities.